Numerical methodologies for the analysis of stone arch bridges with damage under railway loading - Rúben Silva (2022)
This paper reports two nonlinear modelling strategies resorting to FE methodologies to simulate the damage state condition in masonry arch bridges under service loading. The first one consists of a nonlinear simulation of the bridge behaviour using an equivalent continuous homogeneous Drucker-Prager model for the whole structure. The second one combines the potentialities of FEM with discrete crack modelling, to simulate a longitudinal crack opening in the arch barrel. These strategies were applied to a single-arch stone masonry railway bridge and its numerical model were used under static and dynamic loading, adopting a freight train load model defined through a simplified methodology in which the train is represented by a set of moving loads travelling over the bridge. By merging the capabilities of a continuous homogeneous model with a discrete crack modelling, a better representation of a longitudinal crack is achieved, in particular the transversal movement of the arch and spandrel walls. These simplified calibrated numerical FE strategies proved very efficient in nonlinear dynamic analysis under service loading.